2020
DOI: 10.1111/jocd.13590
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ADMA, IMA, and Vitamin A and E Levels in Patients with Acne Vulgaris

Abstract: Background Acne vulgaris is a common skin disease in adolescents known to be associated with oxidative stress. However, the number of studies in which oxidative stress and antioxidants are evaluated together is limited. Aims In this study, we aimed to investigate L‐arginine/nitric oxide (NO) pathway metabolites, ischemia‐modified albumin (IMA), and vitamin A and E levels in patients with acne and its association with disease severity. Patients/Methods Ninety patients with acne and 30 healthy adults were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…They also found that IMA plasma levels increased with disease severity. As the disease progresses, plasma levels of L-arginine, citrulline and vitamin A decrease [38]. According to all these studies, our results show that AV patients have higher IMA levels.…”
supporting
confidence: 70%
“…They also found that IMA plasma levels increased with disease severity. As the disease progresses, plasma levels of L-arginine, citrulline and vitamin A decrease [38]. According to all these studies, our results show that AV patients have higher IMA levels.…”
supporting
confidence: 70%
“…The role of factors such as diet, vitamin D, autoinflammation, obesity, and some biochemical parameters appears to be involved in acne vulgaris 18,19 . A study declared that L‐arginine‐NO, oxidative stress, and ischemia‐modified albumin (IMA) may play a significant role in the progression and pathogenesis of acne vulgaris 20 . The role of survivin in maintaining the viability of epidermal stem cells has been suggested in the past decades.…”
Section: Discussionmentioning
confidence: 99%
“…Under OS conditions, there is an increase in the activity of enzymes responsible for the generation of SDMA and ADMA as well as a decrease in the activity of enzymes involved in their metabolism [89]. The only study that assessed SDMA and ADMA levels in acne patients revealed higher serum levels of these compounds [55].…”
Section: Oxidative Stress Markers Evaluated In Acne Patientsmentioning
confidence: 99%